THE NEEDS ANALYSIS FOR DEVELOPING DIFFERENTIATED STEAMS LEARNING DESIGN BASED ON DESIGN THINKING TO INCREASE CREATIVITY IN PRIMARY SCHOOL - Nur Aini Ochtafiya; Nadi Suprapto; Ganes Gunansyah; Hendratno Hendratno; Nurul Istiq'faroh (Jurnal Cakrawala Pendas, 2025)
STEAMS is 21st century learning approach that aims to teach children the new ways of thinking. The development of differentiated STEAMS learning design based on design thinking by integrating Science, Technology, Engineering, Mathematics, Art and Social can improve students' creativity. This research aims to analyze the needs for the development of differentiated STEAMS learning design. This is based on the priority recommendations of the Education Report and Data-Based Planning (PBD) of the Ministry of Education and Research for SD Muhammadiyah Manyar leading to indicators of improving the quality of learning and creative character of students. The research was conducted with a quantitative descriptive analysis method to obtain the initial needs through data analysis. Data were collected through questionnaires, interviews, and tests. The results showed that needs analysis can be used as a reference in developing differentiated STEAMS learning design based on design thinking. The conclusion of this study obtained three findings related with the differentiated STEAMS learning design development. The first finding is the differentiated STEAMS learning design can fulfil student learning needs. Second, STEAMS can be integrated with differentiated learning. Third, students' creative thinking skills can be improved through integrated Science, Technology, Engineering, Mathematics, Art and Social.